Adaptive thermal comfort in Brazilian schools by Building Performance Simulation (BPS) - Silva, Caio Frederico e (2020)
Building performance simulation (BPS) is a crucial tool towards the design of projects better adapted its climatic context. In this sense, the objective of this research is to evaluate a method of thermal comfort analysis of schools in three Brazilian cities using BPS. The methodological procedures involved a literature review, in which the simulation tool and analysis method were chosen. Following simulations with the software DesignBuilder were performed using as study case a standard school typology designed by the General Coordination of Educational Infrastructure (CODIN/FNDE). This article evaluates its percentage occupied comfort hours in 3 reference cities: Cuiabá-MT, Brasília-DF, and Curitiba-PR. The results show respectively, for the cities of Curitiba, Brasília and Cuiabá, percentages of comfort hours of 76%, 70%, and 23%. The research states that the project must have different strategies for different climates. Finally, this article recommends this method should be applied to other cities and buildings.